2020
DOI: 10.12659/msm.919644
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Prognostic Significance of m6A-Related Genes in Lung Adenocarcinoma

Abstract: Background:Lung adenocarcinoma (LUAD) is the most common subtype of lung malignancy and is the leading cause of cancer-related mortalities worldwide. N6-methyladenosine (m6A), the most prevalent internal modification of mRNAs, plays crucial roles in regulating mRNA splicing, exportation, localization, translation, and stability. This study assessed the expression patterns and prognostic value of m6A-related genes in LUAD. Material/Methods:The expression data of 509 LUAD samples and 20 normal samples were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 38 publications
(38 reference statements)
3
69
0
Order By: Relevance
“…Public dataset acquisition and process were conducted as previously described 33 . The Cancer Genome Atlas (TCGA) database (http://gdc-portal.nci.nih.gov/) and Genotype-Tissue Expression (GTEX) database (https:// gtexportal.org/) were used to analyze the expression of SPATS2 in pan-cancers.…”
Section: Dataset Analysismentioning
confidence: 99%
“…Public dataset acquisition and process were conducted as previously described 33 . The Cancer Genome Atlas (TCGA) database (http://gdc-portal.nci.nih.gov/) and Genotype-Tissue Expression (GTEX) database (https:// gtexportal.org/) were used to analyze the expression of SPATS2 in pan-cancers.…”
Section: Dataset Analysismentioning
confidence: 99%
“…Therefore, there also exist some differences in the significant m6A-related genes for patient outcomes. In LUAD, Zhang Y. et al (2020) demonstrated that METTL3, YTHDF1, and YTHDF2 were identified as prognostic genes and associated with better relapse-free survival (RFS) and OS. Li et al (2020) analyzed the TCGA database combined with the Genotype-Tissue Expression (GTEx) database and calculated the prognostic signature-based risk scores of RBM15, HNRNPC, and KIAA1429.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies on the prognostic role of m6A genes have emerged, including LUAD ( Zhang Y. et al, 2020 ), renal cell carcinoma ( Gao et al, 2020 ), cervical cancer ( Yang et al, 2020 ), colorectal cancer ( Sun et al, 2020 ), and breast cancer ( Wei et al, 2020 ). However, few research focus on LUSC.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this, the authors suggest that YTHDF2 can promote the growth of lung cancer by affecting the pentose phosphate pathway (PPP) ( 34 ). Recent studies have shown that YTHDF1 and YTHDF2 are highly expressed in lung adenocarcinoma and related to the prognosis of patients, but the specific mechanism remains unclear ( 74 ). Data from The Cancer Genome Atlas (TCGA) and Genotype-Tissue Expression (GTEx) database show that both YTHDF1 and YTHDF2 were highly expressed in lung adenocarcinoma ( 75 ).…”
Section: Function Of Yth Domain Family Proteins In Malignant Tumorsmentioning
confidence: 99%